Analysis of serum levels of B cell activating factor and soluble B cell activating factor receptor with disease activity in systemic lupus erythematosus - Raveinal, Raveinal; Elvira, Dwitya; Delfin, Muhamad (Universa Medicina, 2025)
Background Systemic lupus erythematosus (SLE) is caused by B-cell hyperactivity, which stimulates the production of autoantibodies, leading to the formation of immune complexes and resulting in tissue damage. Increased B-cell activation is associated with disease activity in SLE. The cytokine B-cell Activating Factor (BAFF) and its soluble BAFF receptor (sBAFF-R) play a crucial role in B-cell activation and survival. Their serum levels may serve as potential biomarkers for SLE severity. This study aimed to compare serum levels of BAFF and sBAFF-R between SLE patients with mild, moderate, and severe disease activity. Methods A cross-sectional study was conducted involving 33 female SLE patients. Subjects were divided into mild, moderate, and severe disease activity groups. Disease activity was assessed using Mexican Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI) scores. Serum BAFF and sBAFF-R levels were measured using ELISA. Data were analyzed using the Kruskal–Wallis and Mann-Whitney tests. A p-value < 0.05 was considered statistically significant. Results The median serum BAFF level in SLE patients was 0.51 ng/mL, and 4.66 ng/mL in sBAFF-R level.There was a statistically significant difference in serum BAFF and sBAFF-R levels between mild, moderate, and severe disease activity among SLE patients (p<0.0001). Conclusion Increased serum levels of BAFF and sBAFF-R may influence disease activity in SLE. Serum concentrations of BAFF and sBAFF-R were found to be associated with disease severity, including mild, moderate, and severe categories. These findings suggest that serum BAFF and sBAFF-R levels may serve as potential biomarkers for assessing SLE activity.